HYBRID METHOD OF MOMENTS SOLUTION FOR A PERTURBED DIELECTRIC CIRCULAR CYLINDER - Wood, William D. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A hybrid technique is developed? using the integral equation/moment method solution approach with non-free space Green's functions, for a class of scat- tering problems involving nearly-circular 2-D dielectric cylinders under TMz illumination. The technique is applicable to other nearly-canonical 2-D penetrable scatterers, and may be extended to certain 3-D geometries. Applications to several 2-D geometries are demonstrated, with scattering pre- dictions compared to those from a standard moment method code. [Vol. 10, No. 3 (1995), Special Issue on Advances in the Application of Method of Moments to Electromagnetic Radiation and Scattering Problems, pp 47-52